2021
DOI: 10.19088/1968-2021.104
|View full text |Cite
|
Sign up to set email alerts
|

Building Forward Better: Inclusive Livelihood Support in Nairobi’s Informal Settlements

Abstract: For the large population living in Nairobi’s informal settlements, the long-term effects of Covid-19 pose a threat to livelihoods, health, and wellbeing. For those working in the informal sector, who are the lifeblood of the city, livelihoods have been severely supressed by Covid-19 restrictions such as curfews, pushing many into further poverty. This article draws on community data, meetings, and authors’ observations as community organisers, to explore the challenges posed by existing government responses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In many cases, and in line with previous evaluations of such efforts, these new programmes face significant challenges in identifying and delivering benefits and risk reproducing old exclusions (see e.g., Kimani et al 2021). For example, a survey of informal workers in 2020 found that less than half of informal workers received cash or food benefits in 12 cities where governments announced relief measures to support vulnerable groups, while the level of relief provided was insufficient to have a positive impact on food security and coping strategies (Alfers et al 2020).…”
Section: Crisis Relief: New Intersections Old Exclusionsmentioning
confidence: 87%
See 2 more Smart Citations
“…In many cases, and in line with previous evaluations of such efforts, these new programmes face significant challenges in identifying and delivering benefits and risk reproducing old exclusions (see e.g., Kimani et al 2021). For example, a survey of informal workers in 2020 found that less than half of informal workers received cash or food benefits in 12 cities where governments announced relief measures to support vulnerable groups, while the level of relief provided was insufficient to have a positive impact on food security and coping strategies (Alfers et al 2020).…”
Section: Crisis Relief: New Intersections Old Exclusionsmentioning
confidence: 87%
“…Notably, some relief programmes have recognised informal workers as a particularly vulnerable group, while the UN (2020: 9) suggests that basic social protection be extended to informal workers -though with providing clear guidance about how to target these workers. Accordingly, most programmes have targeted relief using pre-existing registers of vulnerable populations without a specific focus on informal workers (e.g., Rateng 2020b; Kimani et al 2021). 15 While some informal workers overlap with groups included in these registers, vulnerability is an imperfect proxy for informality, leading these programmes to exclude significant subsets of informal workers.…”
Section: Inaccessible Crisis Reliefmentioning
confidence: 99%
See 1 more Smart Citation
“…Given informal workers’ histories of disconnection and marginalization from the state and health care, histories of harassment at the hands of state agents, increased crackdowns on informality during the pandemic, and greater risk of exposure to the virus (e.g. Gallien and van den Boogaard, 2021; Kimani et al., 2021; Moussié et al., 2020; Resnick, 2019), some have argued that informality may be linked to low trust in state institutions and public health officials, and that this may have deteriorated further during the pandemic, in turn leading to lower willingness to comply with pandemic‐related health policies (Braham, 2022; Harvey, 2020). Second, the broader literature on marginalization and informality tends to focus on the informal economy, rather than exploring its heterogeneity.…”
Section: Marginalization Trust and Health‐seeking Behaviourmentioning
confidence: 99%
“…For others, the issue is not with the adjective 'better', but rather with the idea of building back something that was there before, with the suggestion that a previous state is to where you want to return. Many scholars thus prefer the expression 'building forward better' (Kimani et al, 2021).…”
Section: 'Building Back Better': a Slogan And A Symbolmentioning
confidence: 99%